EFFECT OF THE ORGANIC PLANT GROWTH REGULATOR (PGR) ON GROWTH AND YIELD OF SOME MUSTARD VARIETIES (Pai-Tsai) (Brassica juncea L.) - Roy Sahala Nababan; Lanna Reni Gustianty; Elfin Efendi (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was conducted on West Bunut Lk. III, West Kisaran, West Kisaran Subdistrict,Asahan District in March into April 2017. The experiment was arranged in Randomized Complete Block Design with two factors and three replication. The first factor is 3 degree of the kind of the mustard variety that is S1 = Sawi Pakchoy Varietas Green Pak Choy, S2 = Sawi Pakchoy Varietas White Pak Choy, S3 = Sawi Kailan Varietas Nova, S4 = Sawi Caisim Varietas Tosakan. Second factor is the gived of ZPT organic that is: Z1 = Tanpa ZPT, Z1= Coconut water (50 ml/l water), Z2 = Onion ectract (50 ml/l air). Parameters were observed is hight plant (cm), production of plant (g), production of plot (kg). The result of the research showed that the use of the best mustard variety treatment have get from Pakchoy mustard Green Pakchoy result hight of plant 14,74 cm, production of plant about 157,30 g and production of plot about 1,51 kg. The best gived ZPT organic treatment have get from onion ectract ZPT result hight of plant 20,33 cm, production of plant about 142,25 g and production of plot 1,36 kg. No intraction of the use the kind of the mustard variety an the gived organic ZPT of the growth and yield mustard plant.